2013
DOI: 10.1186/1472-6882-13-301
|View full text |Cite
|
Sign up to set email alerts
|

Use of alternative medicine for hypertension in Buikwe and Mukono districts of Uganda: a cross sectional study

Abstract: BackgroundUse of alternative medicine for chronic diseases such as hypertension is common in low as well as high income countries. This study estimated the proportion of people who were aware of their hypertension that use alternative medicine and identified factors predicting the use of alternative medicine.MethodsIn a community based cross sectional survey among people ≥ 15 years in Buikwe and Mukono districts of Uganda 258 people aware of their hypertension were questioned about use of alternative medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 34 publications
4
36
1
1
Order By: Relevance
“…The proportion of the use of CAM found in this study 26.1% (95% CI 20.7%-31.8%) is similar to that found by previous studies conducted in sub-Saharan Africa (SSA) [20, 21]. …”
Section: Discussionsupporting
confidence: 89%
“…The proportion of the use of CAM found in this study 26.1% (95% CI 20.7%-31.8%) is similar to that found by previous studies conducted in sub-Saharan Africa (SSA) [20, 21]. …”
Section: Discussionsupporting
confidence: 89%
“…A pretested and validated questionnaire was used for data collection. Questions were adopted according to NCCIH researches and developed through extensive reading of previous literatures . The tool covered four main domains: (1) The demographic information of respondents; (2) Patients' use of CAM and the product used; (3) Patients' behaviour in seeking CAM including reasons, recommendations and expenditure; and (4) Perceptions of adverse effects that may accompany the use of CAM.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers noted that treatment with traditional therapies, particularly herbals, has evolved through ages depending on religions, social beliefs and cultural structure of various societies around the world . Some previous studies have shown an increased prevalence of using herbals and other CAM modalities among hypertensive patients in developing countries as a way of self‐care . These have identified the simultaneous use of CAM products alongside the standard treatment of hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative treatment modalities such as acupuncture and aromatherapy have been used since the third millennium BC. Other more modern interpretations of CAM, such as lifestyle interventions, (Nuwaha & Musinguzi, 2013) are able to provide considerable relief to patients; however, until recently, holistic therapies were not considered appropriate treatment choices due to a paucity of research to support their use. But, more recent medical literature includes a growing body of evidence that validates the efficacy and safety profile of numerous integrative therapies and the popularity of CAM continues to grow.…”
Section: Complementary and Alternative Medi-cine (Cam)mentioning
confidence: 99%